Pengaruh Komposisi Bahan Bakar Campuran Metanol Bensin Terhadap Kinerja Mesin Dan Emisi Gas Buang Pada Motor Yamaha Nmax - Christian Paoki, Kevin Brandon; Ghurri, Ainul; Nindhia, Tjokorda Gde Tirta (Teknik Desain Mekanika; Vol 10 No 4 (2021): Oktober 2021 : Teknik Desain Mekanika, 2021)
Abstract Sooner or later the source of oil (fossil fuel) will run out because petroleum is a non-renewable energy source. Methanol is one of the alternative energy sources that can reduce the use of petroleum. With the addition of methanol in the fuel, the exhaust gases and engine performance will aslo change. The variation of methanol that is mixed with the fuel is 5% (M5), 15% (M15), and 20% (M20). The fuel that has been mixed with methanol is expected to reduce exhaust gasses and increase the torque and power generated by the vehicle's engine. The tests were carried out using Dyno Test Super Dyno 50L engine to determine changes in torque and vehicle power, while the exhaust gases test were using the Muller Beam 10000 MX. The results of the engine performance test show that with the addition of methanol there is a change in the torque and power produced by the vehicle engine. M20 being a mixed fuel that produces the highest maximum torque and power. While the exhaust gases testing shows that by using a mixed fuel M15 there is a decrease in the levels of HC and CO which is the best among the 4 variations of other fuels. Keywords: Methanol, Torque, Power, SFC, HC, CO